Knowledge and perception of medical and pharmacy students toward the usage of sunblock - Ab. Hadi, Hazrina; Elkalmi, Ramadan Mohamed Mahmod; Jamshed, Shazia Qasim; Awadh, Ammar Ihsan JawaD (Elsevier Inc., 2014)
Objectives: To evaluate the knowledge and perception of medical and phar- macy students toward the usage of sunblock as skin protection against ultraviolet (UV). MethOds: This cross-sectional study was conducted among the undergradu- ate final year medical and pharmacy students at the International Islamic University Malaysia (IIUM). Validated questionnaire were used to collect the data. The question- naires were distributed to 134 students from medicine and 100 pharmacy students. Descriptive and inferential statistics are used whenever appropriate. Results: Overall, 161 participants out of a total of 234 completed the questionnaire with 101 medical students (75.4%) and 60 pharmacy students (60.0%). Majority of the respondents were female 64 (63.4%) and 37 (36.6%) were male. The median of knowl- edge scores of the final year medical students was significantly lower than the final year pharmacy students (p<0.01). There is no significant differnce between the knowledge of the female and male students (Mann Whitney U Test value = 0.27, p<0.01). This study reported that 24 (39.3 %) of pharmacy students were influ- enced by the media to use sunblock whereas 35 (34.7%) of medical students had the highest influence from friends to use sunblock. However, this study showed there was no significant difference in the perception of pharmacy and medical studnets p=0.020. cOnclusiOns: In conclusion, the knowledge of pharmacy students is significantly higher than the knowledge of medical students had on the usage of sunblock. Both medical and pharmacy students have the same level of perception towards the usage of sunblock.